2008
DOI: 10.1002/hipo.20476
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxin restores hypothyroidism‐induced impairment of hippocampus‐dependent learning and memory: Behavioral, electrophysiological, and molecular studies

Abstract: Hypothyroidism induces cognitive impairment in experimental animals and patients. Clinical reports are conflicting about the ability of thyroid hormone replacement therapy to fully restore the hypothyroidism-induced learning and memory impairment. In this study, we investigated the effects of L-thyroxin (thyroxin) treatment on hippocampus-dependent learning and memory in thyroidectomized adult rats. In the radial arm water maze (RAWM) task, thyroxin treated thyroidectomized animals made significantly fewer err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 70 publications
8
105
1
Order By: Relevance
“…Reduced levels . In addition, researchers have shown that thyroxine improved performances of rats in a radial arm maze task and ameliorated long-term potentiation impairments in the CA1 area of the hippocampus when it was administered to thyroidectomized rats 21 . These scientific findings support the results of our study that PTU-induced hypothyroidism disrupted learning and memory in both the Morris water maze and passive avoidance tasks in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels . In addition, researchers have shown that thyroxine improved performances of rats in a radial arm maze task and ameliorated long-term potentiation impairments in the CA1 area of the hippocampus when it was administered to thyroidectomized rats 21 . These scientific findings support the results of our study that PTU-induced hypothyroidism disrupted learning and memory in both the Morris water maze and passive avoidance tasks in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The RAWM is a black circular water tub with six V-shaped stainless steel structures arranged to form a swimming field of an open central area and six swim paths (Diamond et al, 1999;Gerges et al, 2004;Alzoubi et al, 2006;Alzoubi et al, 2009). The water temperature was maintained at 248C 6 18C.…”
Section: The Radial Arm Water Maze (Rawm) Proceduresmentioning
confidence: 99%
“…Nicotine, the main component in tobacco, was reported to alleviate impairment of memory associated with psychosocial stress (Aleisa et al, 2006c;Alzoubi et al, 2009b), aging (Carrasco et al, 2006), hypothyroidism (Alzoubi et al, 2005(Alzoubi et al, , 2009a), Alzheimer's disease (Jones et al, 1992;White and Levin, 1999;Srivareerat et al, 2009), Parkinson's disease (Kelton et al, 2000), schizophrenia (Smith et al, 2002;Harris et al, 2004;Jubelt et al, 2008), and attention deficit/hyperactivity disorder (ADHD; Poltavski and Petros, 2006;Potter and Newhouse, 2008). In the hippocampus, nicotine facilitates the induction of LTP in the CA1 region of rat hippocampal slices (Fujii et al, 1999;He et al, 2003) and induces long lasting potentiation in intact mouse DG region (Sawada et al, 1994).…”
Section: Introductionmentioning
confidence: 99%